The effects of hydraulic works and wetlands function in the Salado-River basin (Buenos Aires, Argentina) - Bazzuri, María Elisa (2018)
Man-made activities exert great influences on fluvial ecosystems, with lowland rivers being substantially modified through agricultural land use and populations. The recent construction of drainage canals in the upper stretch of the Salado-River basin caused the mobilization of huge amounts of salts formerly stored in the groundwater. The main aim of this work was to analyze the effect of the discharges of those canals into the Salado-River water, under different hydrologic conditions, and the role of the wetlands and shallow lakes placed along the canals’ system. Physicochemical variables were measured and water samples were taken during times of high water, mean flows, drought, and extreme drought. The environmental variables and the plankton development were related to the hydrologic regime and reached minimum values during floods because of low temperatures and dilution. Local effects on the water’s ionic composition became pronounced during droughts because of groundwater input. Nutrient concentrations were mainly associated with point wastewater discharges. Conductivity, ion concentrations, total plankton biomass, and species richness increased in the Salado-River downstream site, after the canals’ discharges. The artificial-drainage system definitely promotes the incorporation of salts into the Salado-River basin. In this scenario, a careful hydraulic management is needed to take into account this issue of secondary salinization that threatens the economic exploitation of the region. The wetlands present in this study acted as service environments not only helping to reduce salt, nutrient, and suspended-solid concentrations downstream but also contributing a plethora of species and plankton biomass into the Salado-River main course.